The routine use of the Edmonton Classification System for Cancer Pain in an outpatient supportive care center. Issue 5 (October 2015) - Arthur, Joseph; Yennurajalingam, Sriram; Nguyen, Linh; Tanco, Kimberson; Chisholm, Gary; Hui, David; Bruera, Eduardo
Abstract: Objective: There is no standardized and universally accepted pain classification system for the assessment and management of cancer pain in both clinical practice and research studies. The Edmonton Classification System for Cancer Pain (ECS–CP) is an assessment tool that has demonstrated value in assessing pain characteristics and response. The purpose of our study was to determine the relationship between negative ECS–CP features and some pain-related variables like pain intensity and opioid use. We also explored whether the number of negative ECS–CP features was associated with higher pain intensity. Method: The electronic charts of 100 patients at an outpatient supportive care clinic in a comprehensive cancer center were reviewed for variables like patient characteristics, initial ECS–CP assessment, morphine equivalent daily dose (MEDD), opioid rotation, Edmonton Symptom Assessment Score (ESAS), and use of adjuvant analgesics. Results: Some 91 of the 100 charts were eligible for analysis. The most common primary cancer type was gastrointestinal (22.1%). The median pain intensity was 6, and the median MEDD was 45 mg. Neuropathic pain was associated with higher median pain intensity (7 vs. 5, p = 0.007) and median MEDD requirement (83 vs. 30, p = 0.013). Psychological distress was associated with higher median pain intensity (7 vs. 5, p = 0.042). Incident pain was also associated with a trend toward higher pain intensity (6 vs. 5, p = 0.06). A higher number of negative ECS–CP features was associated with higher pain intensity ( p = 0.01). Significance of Results: The ECS–CP was successfully completed in the majority of patients, demonstrating its utility in routine clinical practice. Neuropathic pain and psychological distress were associated with higher pain intensity. Also, neuropathic pain was associated with a higher MEDD. A higher sum of negative ECS–CP features was associated with higher pain intensity. Further studies will be needed to verify and explore these observations.